2013
DOI: 10.1095/biolreprod.113.109207
|View full text |Cite
|
Sign up to set email alerts
|

Role of microRNA-136-3p on the Expression of Luteinizing Hormone-Human Chorionic Gonadotropin Receptor mRNA in Rat Ovaries1

Abstract: MicroRNAs (miRNAs) are small noncoding RNAs that interact with mRNAs and trigger either translation repression or RNA cleavage of target genes. In this study, we investigated whether miRNA was involved in down-regulation of the luteinizing hormone receptor (LHR) in rat ovaries. An miRNA microarray was used to analyze the overall miRNA expression profile of rat ovaries in association with the down-regulation of LHR mRNA. We found that 23 miRNAs were highly expressed during this period. Combining these results w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 53 publications
(55 reference statements)
2
33
0
Order By: Relevance
“…QPCR analyses confirmed that at least three of these miRNAs were also upregulated significantly in some or all of the large healthy follicle categories relative to large atretic follicles, thus identifying this set of miRNAs as very strong candidates with a role in the development of bovine dominant follicles. mir-144, mir-202, mir-451, and mir-652 were reported earlier to be expressed in the ovary (Hossain et al 2009, McBride et al 2012, Kitahara et al 2013, Schauer et al 2013, although their expression patterns within follicular tissues were not studied in detail. In this study, bta-miR-202 was restricted to the bovine gonad; moreover, its expression within the follicle was highest in granulosa cells while levels in ovarian stroma were negligible.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…QPCR analyses confirmed that at least three of these miRNAs were also upregulated significantly in some or all of the large healthy follicle categories relative to large atretic follicles, thus identifying this set of miRNAs as very strong candidates with a role in the development of bovine dominant follicles. mir-144, mir-202, mir-451, and mir-652 were reported earlier to be expressed in the ovary (Hossain et al 2009, McBride et al 2012, Kitahara et al 2013, Schauer et al 2013, although their expression patterns within follicular tissues were not studied in detail. In this study, bta-miR-202 was restricted to the bovine gonad; moreover, its expression within the follicle was highest in granulosa cells while levels in ovarian stroma were negligible.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to mir-202, biological roles for the clustered mir-144 and mir-451 have also been proposed, but only in relation to non-ovarian cells; those include regulatory roles in erythropoiesis (Pase et al 2009), differentiation of vascular smooth muscle cells (Turczyń ska et al 2013) and, potentially relevant during follicular differentiation, cholesterol trafficking in macrophages (Ramirez et al 2013). Interestingly, both miR-144 and miR-451, as well as miR-652, were upregulated in rat ovaries following an ovulatory hCG bolus, although no attempt was made to identify the specific cell type(s) involved (Kitahara et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study performed using whole rat ovary homogenates identifi ed miRNA-136-3p as being overexpressed 6 h after hCG treatment and bioinformatic analyses indicated that 3′-UTR of the rat LHR has a miR-136-3p site within it. The biologic activity of miR-136 was then tested in primary rat granulosa cell culture and was shown to directly target the rat LHr (Kitahara et al 2013 ). It should be noted that bioinformatic (TargetScan) analysis of the human LHr 3′-UTR does not detect a miR-136-3p site within it.…”
Section: Microrna Regulation Within the Ovulatory Folliclementioning
confidence: 99%